Association of Hospital Consolidation with Cancer Outcomes - Justin Graff MD; Mahnoor Ayub BS, MS; Prashanth Prabakaran MD; Brendan Keelan BS; John D. Cramer MD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Hospital mergers have increased significantly since 2010, driven by factors such as healthcare policy changes, reimbursement, economies of scale, and quality improvement goals. However, limited evidence exists about how these mergers affect the quality of care and cancer outcomes. We conducted a difference-in-differences analysis to assess the impact of hospital consolidation on cancer outcomes. Using data from the Surveillance, Epidemiology, and End Results (SEER) program, we identified cancer patients diagnosed between 2008 and 2016, then used the Health Cost Institute’s Healthy Marketplace Index to assess hospital consolidation as measured by the Herfindahl–Hirschman Index (HHI). The HHI is a measure of market concentration and competition between firms in a given industry. We found that increases in hospital consolidation were associated with a higher likelihood of early-stage cancer diagnosis compared to control areas (−1.1%, 95% confidence interval (CI) −2.3 to 0.0%), and improved overall survival (hazard ratio 0.94, CI 0.90-0.98). These improvements were restricted to cancers with screening recommendations. Our study suggests that hospital consolidation may have some benefits for cancer patients. However, these benefits may not be evenly distributed across all cancer types. Further research is needed to confirm these findings and to understand the mechanisms by which hospital consolidation affects cancer outcomes.